Autophosphorylation of the carboxyl‐terminal domain is not required for oncogenic transformation by lung‐cancer derived EGFR mutants. Issue 3 (5th March 2018) - Cho, Jeonghee; Kim, Sujin; Du, Jinyan; Meyerson, Matthew
Abstract : Aberrant activation of cancer‐derived mutants of the epidermal growth factor receptor (EGFR) is closely associated with cancer pathogenesis and is thought to be mediated through multiple tyrosine phosphorylations within the C‐terminal domain. Here, we examined the consequences of the loss of these C‐terminal phosphorylation sites on cellular transformation in the context of lung‐cancer‐derived L858R, exon 19 deletion and exon 20 insertion mutant EGFR. Oncogenic EGFR mutants with substitution of the 10 potential C‐terminal tyrosine autophosphorylation sites for phenylalanine (CYF10) were still able to promote anchorage‐independent growth in soft agar at levels comparable to the parental L858R or exon19 deletion or exon 20 insertion mutants with intact autophosphorylation sites. Furthermore, these CYF10 mutants retained the ability to transform Ba/F3 cells in the absence of IL‐3. Bead‐based phosphorylation and immunoprecipitation analyses demonstrated that key EGFR‐associated proteins—including Grb2 and PLC‐γ—are neither phosphorylated nor bound to CYF10 mutants in transformed cells. Taken together, we conclude that tyrosine phosphorylation is not required for oncogenic activity of lung‐cancer‐derived mutant EGFR, suggesting these mutants can lead to cellular transformation by an alternative mechanism independent of EGFR phosphorylation. Abstract : What's new? Mutations in the epidermal growth factor receptor (EGFR) are common cancer‐driving events that result in ligand‐independent receptor activation and autophosphorylation. Whether autophosphorylation of mutant EGFR is required for transformation, however, is unclear. In this study, lung‐cancer‐derived oncogenic mutant EGFRs lacking 10 potential C‐terminal tyrosine autophosphorylation sites were found to retain the ability to transform cells. Transformation occurred in the absence of IL‐3 ligand. The findings indicate that oncogenic EGFR mutants can be activated independently of autophosphorylation, making their mechanisms of activation distinct from wild‐type EGFR. The results provide mechanistic insight for the understanding of mutant EGFR‐mediated cellular transformation.